British Association for Sexual Health and HIV (BASHH) United Kingdom national guideline on the management of Trichomonas vaginalis 2021. (July 2022) - Sherrard, Jackie; Pitt, Rachel; Hobbs, Kate Russell; Maynard, Michelle; Cochrane, Eleanor; Wilson, Janet; Tipple, Craig
The main objective of this guideline is to assist practitioners in managing individuals diagnosed with Trichomonas vaginalis (TV). It offers recommendations on the diagnostic tests, treatment regimens and health promotion principles needed for the effective management of TV. It covers the management of the initial presentation, as well as how to prevent transmission and future re-infection. It is aimed primarily at people aged 16 years or older presenting to health care professionals, working in departments offering specialist care in sexually transmitted infection (STI) management within the United Kingdom. However, the principles of the recommendations are applicable across all levels of STI care providers (N.B. non-specialist services may need to develop, where appropriate, local care pathways).